Pengaruh Lokasi, Brand Image, Kualitas Produk dan Harga Terhadap Kepuasan Konsumen NIKIKOPI (Studi Kasus Pada Konsumen NIKIKOPI Kab. Sampang) - Al Farisi, Salman; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This investigate was conducted to decide the impact of area, brand picture, item quality and cost on buyer fulfillment (case think about on buyers of NIKIKOPI Rule, Sampang) this inquire about strategy employments a quantitative strategy utilizing non-probability examining strategies whereas the information utilized employments essential information by taking information employing a likert scale questionnaire which is disseminated within the shape of a google shape. Examining in this ponder utilized the Malhotra equation and was found to have a add up to of 85 relawants. It is at the same time known that area, brand picture, item quality and cost have a noteworthy impact on customer fulfillment of NIKIKOPI Sampang Rule. In the mean time, somewhat the cost has an inconsequential impact. Keywords: Area, Brand Picture, Item Quality And Cost